On the question of the mechanism of the general toxic action of lead nitrate - KZh Dakieva (Open Journal of Environmental Biology - Peertechz Publications, 2023)
The leading unfavorable factor in the working environment that affects the health of miners is polymetallic dust, which contains a large number of toxic chemical elements. The study of the chemical composition of the floating dust in the air environment of the quarries of the East Kazakhstan copper-chemical plant and processing plant (Mamyrbaev, Konakbaev, 1992) showed a high content of lead, selenium, antimony, arsenic, and other trace elements.